Smart Europe (Volume 4) - Rifkin, Jeremy (European Investment Bank, 2019)
A green digital economy could change the future of the Old Continent. The new Smart Europe will be based on three elements: new communication technologies, new sources of energy and new modes of mobility. But the transition will require a transformation of the continental infrastructure. Digitalisation, the Internet and renewables will play a major role in the so-called Third and Fourth Industrial Revolutions: sensors embedded in devices will allow an immediate connection between humans and machines, providing updated data and information. Big Data and analytics, used to develop algorithms, will be able to increase productivity, address climate change and diminish the cost of goods and services. Sun, wind and renewable energies will make advanced economies less dependent on fossil fuel and nuclear power, boosting the development of sustainable economic models. Over the last few years, Jeremy Rifkin, advisor to the European Union and main architect of the Third Industrial Revolution long-term economic stability plan, has been promoting the importance of this approach, enabling collaboration in “vast virtual and physical global networks to create a more ecologically sustainable and equitable quality of life”. This is the fourth essay in the Big Ideas series created by the European Investment Bank. The EIB has invited international thought leaders to write about the most important issues of the day. These essays are a reminder that we need new thinking to protect the environment, promote equality and improve people’s lives around the globe.